2017
DOI: 10.1175/jcli-d-16-0025.1
|View full text |Cite
|
Sign up to set email alerts
|

Wind-Driven Atlantic Water Flow as a Direct Mode for Reduced Barents Sea Ice Cover

Abstract: Variability in the Barents Sea ice cover on interannual and longer time scales has previously been shown to be governed by oceanic heat transport. Based on analysis of observations and results from an ocean circulation model during an event of reduced sea ice cover in the northeastern Barents Sea in winter 1993, it is shown that the ocean also plays a direct role within seasons. Positive wind stress curl and associated Ekman divergence causes a coherent increase in the Atlantic water transport along the negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
73
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 68 publications
8
73
0
Order By: Relevance
“…The counterclockwise phase of the Fram‐Barents connection (i.e., anomalous Barents Sea transport towards the Arctic) features a similar low SLP and cyclonic winds in the Nordic Seas as the AO and NAO. The Barents Sea transport is indeed weakly but significantly correlated to both in HiGEM1.1 ( r = 0.3) as also found by Lien et al (). In practice, the anomalous circulation around Svalbard can be facilitated by changing the fraction of the Atlantic Water carried by the Norwegian Atlantic Current that bifurcates into the Barents Sea versus the fraction that continues to feed the West Spitsbergen Current toward the Fram Strait.…”
Section: Discussion: Mechanisms Behind Strait Correlationssupporting
confidence: 85%
See 1 more Smart Citation
“…The counterclockwise phase of the Fram‐Barents connection (i.e., anomalous Barents Sea transport towards the Arctic) features a similar low SLP and cyclonic winds in the Nordic Seas as the AO and NAO. The Barents Sea transport is indeed weakly but significantly correlated to both in HiGEM1.1 ( r = 0.3) as also found by Lien et al (). In practice, the anomalous circulation around Svalbard can be facilitated by changing the fraction of the Atlantic Water carried by the Norwegian Atlantic Current that bifurcates into the Barents Sea versus the fraction that continues to feed the West Spitsbergen Current toward the Fram Strait.…”
Section: Discussion: Mechanisms Behind Strait Correlationssupporting
confidence: 85%
“…The opposite happens for a counterclockwise anomalous circulation around Svalbard. This mechanism has also been identified in observations on multiple timescales, from daily to interannual (Bader et al, ; Chafik et al, ; Lien et al, ; Lien et al, ). The counterclockwise phase of the Fram‐Barents connection (i.e., anomalous Barents Sea transport towards the Arctic) features a similar low SLP and cyclonic winds in the Nordic Seas as the AO and NAO.…”
Section: Discussion: Mechanisms Behind Strait Correlationsmentioning
confidence: 61%
“…It has also been suggested that the NAO affects the volume of AW entering the Barents Sea and hence the fraction of water that recirculates or reaches the FS. Furevik (), Lien et al (), and J. Zhang et al () showed that during periods with strong NAO, the AW inflow was stronger and had an anomalous eastward extension, resulting in less water being recirculated in the Nordic Seas and more entering the Barents Sea. However, Ingvaldsen et al () and Lien et al () found that the flow through the BSO is also highly dependent on the local wind pattern and positive wind stress curl in the Barents Sea which in turn sets up Ekman transport toward the coast.…”
Section: Introductionmentioning
confidence: 99%
“…Furevik (), Lien et al (), and J. Zhang et al () showed that during periods with strong NAO, the AW inflow was stronger and had an anomalous eastward extension, resulting in less water being recirculated in the Nordic Seas and more entering the Barents Sea. However, Ingvaldsen et al () and Lien et al () found that the flow through the BSO is also highly dependent on the local wind pattern and positive wind stress curl in the Barents Sea which in turn sets up Ekman transport toward the coast. Finally, Smedsrud et al () found that the NAO correlation broke down after 2000, and Lien et al () showed that the flow into the BSO was strongly affected by northern Barents Sea winds.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have addressed the mechanism of SIC change in winter [10,11]. The roles of radiation and sensible heat [8,12], moisture transport [13,14], wind-driven sea ice drifting [15,16] and other factors [17] have been examined in many previous studies.…”
Section: Introductionmentioning
confidence: 99%